FINITE ELEMENT ANALYSIS OF WELDING RESIDUAL STRESS FIELD OF DUAL CLUTCH TRANSMISSION INNER PLATE CARRIER - LIU ChunZhen; CHU ChaoMei; GU JianHua (Jixie qiangdu)
In view of the structural failure caused by laser welding residual stress, with the target DCT dual clutch transmission inner plate carrier and the spline as the study object,a three-dimensional finite element numerical model was established by SYSWELD finite element software and the numerical simulation of the welding process was carried out. The thermal cycle curves of the transient temperature field and characteristic points were obtained, the characteristics of the weld seams were basically in line with the actual welding seams. On this basis, the evolution of the metallurgical structure and the distribution of the residual stress in the weld were obtained.The results show that the microstructure of the weld area after cooling is mainly martensite, and the welded joint has good strength and toughness. The tangential residual stress reaches the peak value of tensile stress at about 2 mm from the center of the weld. This is where the weld is most vulnerable to the crack.